2016
DOI: 10.1111/desc.12455
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potential differences in children supplemented with long‐chain polyunsaturated fatty acids during infancy

Abstract: Long-chain polyunsaturated fatty acids (LCPUFA) have been shown to be necessary for early retinal and brain development, but long-term cognitive benefits of LCPUFA in infancy have not been definitively established. The present study sought to determine whether LCPUFA supplementation during the first year of life would result in group differences in behavior and event-related potentials (ERPs) while performing a task requiring response inhibition (Go/No-Go) at 5.5 years of age. As newborns, 69 children were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 95 publications
4
27
0
1
Order By: Relevance
“…These results are also consistent with results of ERPs to Go/No-Go stimuli in the same cohort when they were tested at 5.5 years of age (Liao et al, 2017). ERP responses of children in the LCPUFA-supplemented group showed the expected differences between Go and No-Go stimuli, while those in the control group did not, again reinforcing the hypothesis that attention and inhibition systems are vulnerable to early life LCPUFA insufficiency.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are also consistent with results of ERPs to Go/No-Go stimuli in the same cohort when they were tested at 5.5 years of age (Liao et al, 2017). ERP responses of children in the LCPUFA-supplemented group showed the expected differences between Go and No-Go stimuli, while those in the control group did not, again reinforcing the hypothesis that attention and inhibition systems are vulnerable to early life LCPUFA insufficiency.…”
Section: Discussionsupporting
confidence: 90%
“…Additional long-term follow up studies found that early life supplementation had positive effects on several important measures of executive function during early childhood and on measures of IQ at the threshold of school age (Colombo et al, 2013). At age 5.5 years, children in the supplemented groups showed differences in brain electrophysiologic responses while performing a task requiring response inhibition (Liao et al, 2017). These studies established that manipulation of the diet in the first year of life had a long-term effect on cognitive and brain functional outcomes, especially for mechanisms related to attention, rule learning and inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies reported no effect of the DHA/ARA supplementation during the first year of life on neurodevelopmental outcomes at 18 months of age in infants from Dallas ( n = 117) [ 9 ] and in infants from Kansas City ( n = 81) [ 8 ]. However, the children that received the DHA/ARA supplemented formula in infancy at the Kansas City site performed better on neurodevelopmental tests in a long term follow up study at 3–5 years of age ( n = 81) [ 10 ] and showed differences in brain electrophysiology at 6 years of age ( n = 69) [ 35 ]. Similarly, a multicenter European trial of DHA and ARA supplementation of infants ( n = 147) during the first four months of life reported no effects of the supplementation on IQ at six years of age but did report that the supplemented children were faster at processing information than the unsupplemented children [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cognitive tests where the correct response is no response, as in the no-go phase of a go/no-go test, brain electrical activity provides a way to assess inhibitory control [36]. One such measure is the event-related potential (ERP) [37].…”
Section: Early Life Exposure To Dha and Ara Results In Long-term Diffmentioning
confidence: 99%